Pengaruh Senam Hamil Yoga Terhadap Kadar Endorphin Plasma dan Tingkat Kecemasan pada Ibu Primigravida Trimester III - Lilis Candra Yanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Women in pregnancy experience many changes, both physical and psychological so that it will make anxiety levels increase and happiness hormones decrease, especially in primigravid mothers before delivery. Aim: Measure endorphin levels and anxiety levels of the third trimester of the primigravida mother. Method: Metode uses a quasi-experiment design with pretest-posttest control group design. The sample was 13-trimester primigravida pregnant women in the intervention group and 13 people in the control group according to inclusion and exclusion criteria. Measurement of anxiety levels using questionnaires with the HAR-S method while measurement of plasma Endorphin levels was done by testing pre and post-blood samples. Data analysis uses the T-test and the Mann-Whitney test. Results: The results showed that there was an influence of yoga on endorphin levels and there was an influence of yoga on anxiety levels. Thus, there is an effect of yoga on endorphin levels and anxiety levels in pregnant women primigravida trimester III. Conclusion: Pregnant gymnastics yoga increases endorphin levels and lowers anxiety levels in the third-trimester primigravida mother